Analysis of the Impact of Boiler Performance Due to the Addition of Water Tubes in a Vertical Fire-Tube Boiler with a Steam Capacity of 100 Kg/Hour - Syahputra, Beni; Syah, Khairudin; Gultom, Aprijal; Gafur, Abdul (ABEC Indonesia, 2024)
The problem with this boiler is that the steam produced is not continuous, meaning that at a pressure of 1 bar, thesteam lasts for approximately 2 minutes, and the heating process of this fire-tube boiler is also prolonged, taking around 95minutes from the start until reaching a temperature of 100°C. This results in the need for more used oil as fuel. Some initialanalyses to solve these issues include increasing the heating surface area of the boiler or the combustion chamber by adding watertubes and using wood as the fuel. The objective of this research is to analyze the heating time, steam retention time, wood f uelconsumption, and efficiency before and after the modification with the addition of water tubes. The method used is experiment al.The tests conducted before modification showed a heating time of 45 minutes, and with the addition of water tubes, the heatingtime was reduced to 36 minutes. The steam retention time before modification was 4 minutes, while with the addition of watertubes, it increased to 4 minutes and 42 seconds. The total wood fuel consumption for the fire-tube boiler to reach an operatingpressure of 3 bar required 33.2 kg of wood, and after the addition of water tubes, the total consumption to reach 3 bar wasreduced to 27 kg of wood. The efficiency of the fire-tube boiler before modification at 1 bar pressure was 66.6%, at 2 barpressure 59.3%, and at 3 bar pressure 51.6%. After adding water tubes to the fire-tube boiler, the efficiency increased, with theefficiency at 1 bar pressure being 74.5%, at 2 bar pressure 68.8%, and at 3 bar pressure 62.9%. This indicates that the addition ofwater tubes can improve the boiler's efficiency.